The Bible as theatre - Levy, Shimon, 1943- (Sussex Academic Press, 2022)
Although the Old Testament has been thoroughly analyzed as literature, and many of its highly dramatic chapters, stories, poetry and prophecies have been adapted for theatre, the Bible as Theatre has hardly been dealt with. As a "threshold-medium", ancient theatre hovered between the holy and the profane. The hostility the Hebrews expressed toward the "indecencies" of theatre was the result of religious, cultural and economic oppression they suffered from Greeks, Romans and other peoples whose theatre was well developed. This book shows that the real fear the ancient Hebrews felt was not of the gaudy aspects of theatre but of its highly creative potential as a rival Creator. A close reading of the OT exposes a refined sense of theatricality, in the usage of space, lighting, costumes and props. God, in theatrical terms, is The Great Offstage Being, in whose name and for whose glory the action is performed.